Dramatização on-line: psicoterapia da relação e psicodrama interno no psicodrama contemporâneo - Vidal, Gabriela Pereira; Cardoso, Alexandra Sombrio (Revista Brasileira de Psicodrama, 2020)
The purpose of this article is to show the possibilities of online psychodrama through the relationship psychotherapy method and the internal psychodrama technique. It deals with a case study with a description of two sections of a patient under the psychotherapeutic process in an online environment. In the first section, the protagonist shows her distresses related to self-perception, which we worked through relational psychotherapy. In the second section, she evidenced her frightening experiences of her childhood reframed through the internal psychodrama. The method of relationship psychotherapy as a powerful tool to work with relationships and distresses, and the internal psychodrama with an effective technique in frightened views, because they allowed working with internalized roles and symbolic actions for a re-registration.